Kolaborasi Cerdas: Mengoptimalkan Pendidikan Melalui Kerja Tim - Hasni, Walidatil; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the smart collaboration carried out by teamwork to optimize education and learning in schools. This type of research approach is qualitative which is implemented through the literary review method. This research synthesizes various relevant references such as articles, books, and other documents to answer research errors. Data collection techniques are carried out through articles sourced from Google Scholar and then analyzed. Qualitative data analysis techniques are used that consist of data reduction, data presentation, and conclusions. The results of data analysis show that teamwork management involves the process of planning, implementing, and supervising team members to work together, communicate effectively, and build trust to achieve coordinated collective action to achieve all targets efficiently. The success of managing team performance depends on good cooperation. With solid teamwork, organizations can solve problems quickly and precisely.